2017
DOI: 10.1371/journal.pone.0178333
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics analysis of the aggregation propensity of polyglutamine segments

Abstract: Protein misfolding and aggregation is a pathogenic feature shared among at least ten polyglutamine (polyQ) neurodegenerative diseases. While solvent-solution interaction is a key factor driving protein folding and aggregation, the solvation properties of expanded polyQ tracts are not well understood. By using GPU-enabled all-atom molecular dynamics simulations of polyQ monomers in an explicit solvent environment, this study shows that solvent-polyQ interaction propensity decreases as the lengths of polyQ tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…However, this ensemble did not match well with the experimental result, probably due to the force field that caused this mismatch. So we did another 4 conventional MD simulations using AMBER ff99SB force field 62,63 and 500-ns duration for each simulation. Different approaches have been proposed for deriving representative ensembles such as ENSEMBLE that assigns weights to the different conformations of the pool 35,36 , and ASTEROIDS that relies on a genetic algorithm to select sub-ensembles 37,38 .…”
Section: Methodsmentioning
confidence: 99%
“…However, this ensemble did not match well with the experimental result, probably due to the force field that caused this mismatch. So we did another 4 conventional MD simulations using AMBER ff99SB force field 62,63 and 500-ns duration for each simulation. Different approaches have been proposed for deriving representative ensembles such as ENSEMBLE that assigns weights to the different conformations of the pool 35,36 , and ASTEROIDS that relies on a genetic algorithm to select sub-ensembles 37,38 .…”
Section: Methodsmentioning
confidence: 99%
“…This additional cost of forming β -sheet structure in the dimer will contribute to the energy barrier that must be surmounted to nucleate a fibril. Despite the fact that each of the three force fields has been favorably evaluated for simulations of polyglutamine (41)(42)(43)(44)(45), they yielded widely different results (Fig. 3d, Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We observed an antiparallel β‐sheet in the four models Q 34 , Q 35 , Q 36 , and Q 40 , whereas in the Q 50 model one parallel and one antiparallel β‐sheet was found. This observation is consistent with the previous study which reveals that the propensity to form β‐sheet content is high when the Q length increases . We also looked into the models with the presence of proline residues and found that these residues did not show much difference in the secondary structure and transformation.…”
Section: Introductionmentioning
confidence: 99%
“…This observation is consistent with the previous study which reveals that the propensity to form β-sheet content is high when the Q length increases. 30 We also looked into the models with the presence of proline residues and found that these residues did not show much difference in the secondary structure and transformation.…”
Section: Introductionmentioning
confidence: 99%